2022
DOI: 10.1111/1440-1703.12313
|View full text |Cite
|
Sign up to set email alerts
|

Intermediate dispersal hypothesis of species diversity: New insights

Abstract: The origin and patterns of species diversity are fundamental themes in ecology and evolutionary biology. Insular systems play an important role in biogeography, and the species richness within an insular system has classically been considered as determined by the balance between the rate of speciation plus net migration and the rate of species extinction. A recent wave of studies integrating comprehensive phenotypic, phylogenetic, and environmental data is accumulating additional macroevolutionary insights at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 100 publications
0
10
0
Order By: Relevance
“…This pattern suggests that dispersal ability is a reliable indicator of gene flow. If dispersal abilities, or proxies thereof, are high, then species will tend towards panmixia (Yamaguchi, 2022). In contrast, lower dispersal abilities will result in populations subdividing across geographic barriers in the landscape (Yamaguchi, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This pattern suggests that dispersal ability is a reliable indicator of gene flow. If dispersal abilities, or proxies thereof, are high, then species will tend towards panmixia (Yamaguchi, 2022). In contrast, lower dispersal abilities will result in populations subdividing across geographic barriers in the landscape (Yamaguchi, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…If dispersal abilities, or proxies thereof, are high, then species will tend towards panmixia (Yamaguchi, 2022). In contrast, lower dispersal abilities will result in populations subdividing across geographic barriers in the landscape (Yamaguchi, 2022). This association is most obvious in species occupying heterogeneous landscapes with many barriers to dispersal.…”
Section: Introductionmentioning
confidence: 99%
“…Spatial processes, such as how islands are geographically arranged, could be a third explanation for the observed patterns. This argument does not necessarily require invoking selection against dispersal ability, and it could easily arise with intermediate dispersal (Ashby et al, 2020; Yamaguchi, 2022). Most likely a great speciator pattern would arise from a combination of spatial, abiotic and biotic factors, but the relative importance of each factor is currently unknown.…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, high dispersal ability allows species to expand and reach large range sizes rapidly, possibly reducing the influence of age on range expansion and size. On the other hand, high dispersal ability prevents speciation and, thereby, range splitting, by maintaining gene flow among populations (Mayr 1963, Yamaguchi 2022). Indeed, dispersal ability positively affects range size (Alzate & Onstein 2022), and we found that for all clades examined and for species of similar age, those with higher dispersal abilities had larger ranges than species with lower dispersal abilities (Fig.…”
Section: Geographical Constraints On the Relationship Between Evoluti...mentioning
confidence: 99%